2017
DOI: 10.1039/c7gc00267j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of isoquinolines in water by a Pd-catalyzed tandem reaction of functionalized alkylnitriles with arylboronic acids

Abstract: Pd-catalyzed tandem reaction of functionalized alkylnitriles with arylboronic acids for the synthesis of diverse isoquinolines in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…[159][160] The mechanism follows a radical pathway which was initiated by the formation of bromodifluoroacetate radical A. Subsequent reactions of A and vinyl isocyanide 28 leads to the formation of cyclohexadienyl radical intermediate C. Again in 2017, Qi et al reported the identical reaction conditions for the successful conversion of 2-(2-oxo-2-arylethyl)benzonitrile 266 with arylboronic acids 197 as reported earlier by Hu et al [157] Additionally, authors have extended scope of this reaction conditions for the synthesis of isoquinolones 268 (Scheme 160). [161] Xiong et al have put forth a Pd-catalyzed C(sp 2 )-H aminoimidoylation of isocyanide vinyl esters 142 towards the synthesis of amino substituted isoquinoline 270.…”
Section: Pd-catalyzed Isoquinoline Synthesismentioning
confidence: 71%
See 1 more Smart Citation
“…[159][160] The mechanism follows a radical pathway which was initiated by the formation of bromodifluoroacetate radical A. Subsequent reactions of A and vinyl isocyanide 28 leads to the formation of cyclohexadienyl radical intermediate C. Again in 2017, Qi et al reported the identical reaction conditions for the successful conversion of 2-(2-oxo-2-arylethyl)benzonitrile 266 with arylboronic acids 197 as reported earlier by Hu et al [157] Additionally, authors have extended scope of this reaction conditions for the synthesis of isoquinolones 268 (Scheme 160). [161] Xiong et al have put forth a Pd-catalyzed C(sp 2 )-H aminoimidoylation of isocyanide vinyl esters 142 towards the synthesis of amino substituted isoquinoline 270.…”
Section: Pd-catalyzed Isoquinoline Synthesismentioning
confidence: 71%
“…Based on these findings, it was proposed that catalytic cycle involves carbopalladation of C(sp 3 )-cyano group followed by intramolecular cyclization (Scheme 158). [157] A similar type of strategy was reported recently by Zhen et al to access aminoisoquinolines and isoquinolones under Nickel-catalyzed reaction conditions. [158] Liu et al reported the synthesis of 1-difluoroalkylated isoquinolines 144 via Pd-catalyzed radical cascade reactions.…”
Section: Pd-catalyzed Isoquinoline Synthesismentioning
confidence: 82%
“…Very recently, our group and others have achieved several tandem transformation of functionalized nitriles with arylboronic acids for access to N ‐heterocycles. For example, palladium‐catalyzed tandem addition/cyclization of 2‐(cyanomethyl)benzonitriles (Scheme b) and methyl 2‐(cyanomethyl)benzoates (Scheme c) with arylboronic acids for the synthesis of isoquinolines and isoquinolones via catalytic carbopalladation of nitriles, respectively. Nickel, as a first‐row transition‐metal in the same group as that of palladium, has attracted significant attention due to its low cost and abundance, meeting the requirements for sustainable chemical synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of an efficient method that can incorporate the nitrogen atom of nitriles into N -heterocycle products by intramolecular cyclization, rather than hydrolysis of ketamine intermediates, still remains a longstanding challenge. In 2017, we have successfully developed a tandem addition and cyclization strategy for the synthesis of isoquinolines and isoquinolones via catalytic carbopalladation of nitriles [24,25].…”
Section: Introductionmentioning
confidence: 99%